2016
DOI: 10.1016/j.cgh.2016.05.045
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Gastric Cancer Among Patients With Intestinal Metaplasia of the Stomach in a US Integrated Health Care System

Abstract: In an analysis of patients with GIM listed in the Kaiser Permanente Southern California database, 2.7% were diagnosed with gastric cancer; almost 70% of cases of gastric cancer were detected at the time of GIM diagnosis. Family history and extensive metaplasia were associated with an increased risk of subsequent gastric cancer. Targeted surveillance of patients with these criteria could increase early detection of gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 14 publications
1
54
1
Order By: Relevance
“…In the present study, the relationship between gastric cancer and GIM is clear, particularly type III of IM, which is associated with the incidence of the aggressive form of stomach cancer [3841]. As a premalignant lesion of gastric carcinoma, GIM has received much attention [42, 43].…”
Section: Discussionmentioning
confidence: 94%
“…In the present study, the relationship between gastric cancer and GIM is clear, particularly type III of IM, which is associated with the incidence of the aggressive form of stomach cancer [3841]. As a premalignant lesion of gastric carcinoma, GIM has received much attention [42, 43].…”
Section: Discussionmentioning
confidence: 94%
“…Two retrospective cohort studies from the USA have identified three risk factors associated with the subsequent development of gastric cancer including family history of gastric cancer, Hispanic ethnicity and extensive GIM . However, the sub‐type of GIM which may be an important risk factor was not assessed.…”
Section: Discussionmentioning
confidence: 99%
“…However, the optimal early gastric cancer detection protocol in low prevalence of gastric cancer regions (5‐7/100 000) has never been established. Strategies to select high‐risk patient for surveillance endoscopy in daily clinical practice have been proposed . .…”
Section: Introductionmentioning
confidence: 99%
“…For example, among individuals from a large integrated health care plan in Southern California, the cumulative 5-year risk for gastric cancer was estimated to be 0.9% (95% CI, 0.3%-1.6%). 15 The pooled annual rate of progression to gastric cancer among individuals with GIM was estimated to be 0.16% per year. This estimate is lower than the previously reported pooled annual cumulative risk of 0.33% for esophageal adenocarcinoma among patients with non-dysplastic Barrett's esophagus, a condition for which endoscopic surveillance is often routinely recommended.…”
Section: Very Lowmentioning
confidence: 99%